2006
DOI: 10.1093/jn/136.5.1305
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Concentration of the Conjugated Linoleic Acid, cis-9,trans-11, in Milk Fat Has Antiatherogenic Effects in Hyperlipidemic Hamsters

Abstract: Milk fat is usually considered to be proatherogenic, although its fatty acid composition can vary, due mainly to farming conditions. No study has evaluated whether such variation can modify the atherogenic properties of dairy fat. Aortic lipid deposition and related risk factors were examined in Syrian hamsters fed diets for 12 wk containing 200 g/kg of 2 commercial milk fats [high content of saturated fatty acids (HSF) and low content of saturated fatty acids (LSF)] contrasting, respectively, in total saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
2
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 27 publications
1
46
2
3
Order By: Relevance
“…Atherogenic outcome was 45 positively associated with several conventional plasma biomarkers of atherogenic risk, such 46 as total plasma cholesterol, triglycerides, or LDL cholesterol 19,30 . These results agree with 47 other observations 7,31 and validate our model of diet-induced atherogenesis. Not surprisingly, 48 these plasma lipids also corresponded to the NMR signals found positively associated with 49 the severity of atherosclerosis, which substantiates our metabonomic approach to find early 50 A c c e p t e d M a n u s c r i p t 8 8 atherogenic biomarkers.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Atherogenic outcome was 45 positively associated with several conventional plasma biomarkers of atherogenic risk, such 46 as total plasma cholesterol, triglycerides, or LDL cholesterol 19,30 . These results agree with 47 other observations 7,31 and validate our model of diet-induced atherogenesis. Not surprisingly, 48 these plasma lipids also corresponded to the NMR signals found positively associated with 49 the severity of atherosclerosis, which substantiates our metabonomic approach to find early 50 A c c e p t e d M a n u s c r i p t 8 8 atherogenic biomarkers.…”
supporting
confidence: 91%
“…Diet and water were available ad libitum, and the cheeses 45 were provided by Lactalis (Retiers, France). The fatty acid compositions of the various 46 products and of the basal diet are listed in Tables 1, 2 Whole aortic lipids were extracted and analyzed by gas liquid chromatography using a 11 high temperature non-polar capillary column 7,19 . Whole aortic cholesteryl esters were taken 12 as an indicator of early atherogenesis (fatty streaks) 19,20 , and expressed as a % of the tissue 13 phospholipids.…”
Section: Oct 1987 Ministry Of Agriculture) Forty-eight Male Goldmentioning
confidence: 99%
See 2 more Smart Citations
“…CLA has been considered anticarcinogenic and antiatherosclerotic at concentrations of 0.5-1% in the diet of animals [33]. Valeille et al [40] suggested that the atherogenic potential of milk fat can be greatly reduced in products with a naturally high content of c 9 t 11 content. Although CLA isomers have different physiological effects, ingestion of c 9 t 11 and/or t 10 c 12 CLA isomers decreased plasma lipid concentrations (cholesterol and TG) in Wistar rats [12].…”
Section: Discussionmentioning
confidence: 99%